Experimental Study of the Performance of Compound Parabolic Concentrating Solar Collector - Abdul-Ghafour, Qussai Jihad; Hassan, Mohammed Aziz (Al-Khwarizmi Engineering Journal, 2016)
The design, construction and investigation of experimental study of two compound parabolic concentrators (CPCs) with tubular absorber have been presented. The performance of CPCs have been evaluated by using outdoor experimental measurements including the instantaneous thermal efficiency. The two CPCs are tested instantly by holding them on a common structure. Many tests are conducted in the present work by truncating one of them in three different levels. For each truncation the acceptance half angle (θc) was changed. Geometrically, the acceptance half angle for standard CPC is (26o). For the truncation levels for the other CPC 1, 2 and 3 the acceptance half angle were 20o, 26o and 59o, consequently. A significant difference between the instantaneous thermal efficiency of 3.86× CPC (θc=20o) and 2.32× CPC (θc=26o), and between that for 3.61× CPC (θc=26o) and 2.32× CPC (θc=26o). It’s noticed that the difference between the instantaneous thermal efficiency of 2.32× CPC (θc=59o) and 2.32× CPC (θc=26o) is small compared with the difference of the first and second cases, the instantaneous thermal efficiency of 2.32× CPC (26o) was higher than those for other three CPCs. The experimental results show that the maximum thermal efficiency of the full 2.32×CPC (26o) is 0.708, the maximum thermal efficiency of the 3.93×CPC (15o), when it’s truncated to 3.84× CPC (20o), 3.61× CPC (26o) and 2.32× CPC (59o) are 0.51, 0.52 and 0.66, respectively. As the concentration ratio decreases from (3.93× to 1×), the thermal efficiency, energy losses and optical efficiency increase from (0.47 to 63), (1.58 to 7.2 K.m2/W) and (0.494 to 0.797), respectively.